John Verse by Verse. - Osborne, Grant R. (Osborne New Testament Commentaries., 2018)
John is at once the most complex and the easiest to understand of all the Gospels. If we want a young seeker or new believer to read something that is both clear and filled with the gospel and good basic theology, we give them the Gospel of John. And if we want to study an incredibly deep theological masterpiece that stretches the brightest mind, we open the Gospel of John. It is the most evangelistic account of Jesus' life and ministry, and it also gives the mature Christian deep theological truths to chew on. In John Verse by Verse, respected New Testament scholar Grant R. Osborne invites the reader to become caught up in the dramatic masterpiece of the Fourth Gospel. He writes, "If I were teaching a course in college or seminary on creative writing, John's Gospel would be set alongside Shakespeare as models of brilliant characterization and plot." It is perhaps Osborne's favorite book of the Bible, and enthusiasm for it shines on every page. The Osborne New Testament Commentaries, by respected professor and author Grant R. Osborne, are for people seeking a straightforward explanation of the text in its context, avoiding either oversimplification or technical complexity. Osborne brings out the riches of the New Testament, making each book accessible for pastors and all who consider themselves students of Scripture.